Feasibility study of a double-step hydroforming process for fabrication of fuel cell bipolar plates with slotted interdigitated serpentine flow field. Issue 1 (July 2016) - Mohammadtabar, N.; Bakhshi-Jooybari, M.; Hosseinipour, S.; Gorji, A.
Abstract Bipolar plate is considered as one of the main components of a fuel cell which has high weight and cost in the manufacturing of fuel cells. These plates are manufactured by different processes such as stamping, rubber pad forming, electromagnetic forming, and hydroforming, each of which has its own specific limitations. Among these processes, hydroforming is considered as a practical method in forming bipolar plates with complicated pattern due to its significant advantages. Bipolar plates have different flow field patterns including parallel, pin type, interdigitated, and serpentine patterns. Forming of slotted interdigitated serpentine flow field is very difficult due to its high geometrical complexity and accuracy of the flow pattern, small distance between slots, and very low thickness of sheet. To overcome this problem, a double-step hydroforming process is proposed in this work: an initial hydroforming step on a concave die and a final hydroforming step on a convex die. It is shown that the double-step hydroforming process is a feasible technique for fabricating metallic bipolar plate of proton exchange membrane (PEM) fuel cells with thin slotted interdigitated serpentine pattern.